ANALISA KETERDAPATAN AKUIFER AIR BAWAH TANAH DENGAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DESA TUNTUNGAN II DUSUN I - Panjaitan, Natalius; Tambun, Bungaran; halawa, analiser (LPPM ISTP, 2024)
Clean water is still a problem in the city of Medan and Deli Serdang Regency according to the North Sumatra Provincial government in the Medan area and its surroundings, the total need for clean water is 11,000 liters/second and an additional water supply of 4,000 liters/second is needed with water availability of 200 liters/second. So that the water supply in the Medan city area and its surroundings still lacks a water supply of 3,800 liters/second article sumutprov.go.id (https://sumutprov.go.id/artikel/artikel/resmikan-programmaster-meter-di-medan–gubernur–edy-rahmayadi-targetkan-tuntaskan–kebutuhan-air-bersih-di-akhir-periode) Besides that, in Tuntungan II Village, Hamlet I, Pancur Batu District, Deli Serdang Regency, there is no water channel from government institutions (PDAM) so that the community's water source in this area is obtained from water from wells/dug wells. this makes this research carried out. to interpret the presence of groundwater which can be used as a source of clean water in the research area conducted in Desa Tuntungan II , Dusun I, Kecamatan Medan Tuntungan, Kota Medan, North Sumatra Province. From the results of data processing, then interpretation of the data is carried out. Data interpretation is done by comparing the RMS table with the rules of the resistivity table of Suyono (1978), Astier (1971) and the geological map of the study area to determine the type of rock. The stratigraphy of the research location according to the resistivity value is thought to consist of 5 lithologies, namely Overburden (24.9-32.4Ω), andesite (1428-1473 Ω), clay (6.45-14.2Ω), andesite breccia (148-170 Ω), tuff (37.6 -74.6 Ω). The existence of a water-carrying layer (aquifer) at the point of measurement Point I is at a depth of around 14.8 – 76.1 meters. The predicted layer thickness is 61.2 m. The lithology of this layer is tuff as a water-carrying layer (aquifer). The existence of a water-carrying layer (aquifer) at Point II is at a depth of around 11.1 – 91.3 meters. The thickness of the layer is 80.2 meters. The lithology of this layer is a strong tuff as a water-carrying layer (aquifer).